2016
DOI: 10.3233/jad-150767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anserine/Carnosine Supplementation on Verbal Episodic Memory in Elderly People

Abstract: Our goal in this study was to determine whether or not anserine/carnosine supplementation (ACS) is capable of preserving cognitive function of elderly people. In a double-blind randomized controlled trial, volunteers were randomly assigned to an ACS or placebo group at a 1:1 ratio. The ACS group took 1.0 g of an anserine/carnosine (3:1) formula daily for 3 months. Participants were evaluated by psychological tests before and after the 3-month supplementation period. Thirty-nine healthy elderly volunteers (60–7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 40 publications
5
96
0
Order By: Relevance
“…For example, oral administration of anserine (10 or 100 mg/45 kg BW in 20 ml of tap water) reduced blood glucose levels during an oral glucose tolerance test in humans . Similarly, supplementing anserine plus carnosine (1 g/day, 3:1 ratio, 3 months) to healthy elderly subjects has been shown to preserve verbal episodic memory and brain perfusion (including blood flow in the prefrontal brain (Ding et al 2018;Hisatsune et al 2015;Rokicki et al 2015), attenuate cognitive impairment (Hisatsune et al 2016;Masuoka et al 2019), inhibit the production of inflammatory cytokines by peripheral blood mononuclear cells (Katakura et al 2017), and enhance muscular strength and exercise endurance (Hirohiko et al 2006). Because avian muscle contains a large amount of anserine as noted previously, much evidence shows that consumption of a popular Asian food known as chicken essence (chicken meat extract) by humans, particularly elderly subjects, has long been a nutritional means to improve human health and prevent chronic diseases.…”
Section: Health Benefits Of Anserine Supplementationmentioning
confidence: 99%
“…For example, oral administration of anserine (10 or 100 mg/45 kg BW in 20 ml of tap water) reduced blood glucose levels during an oral glucose tolerance test in humans . Similarly, supplementing anserine plus carnosine (1 g/day, 3:1 ratio, 3 months) to healthy elderly subjects has been shown to preserve verbal episodic memory and brain perfusion (including blood flow in the prefrontal brain (Ding et al 2018;Hisatsune et al 2015;Rokicki et al 2015), attenuate cognitive impairment (Hisatsune et al 2016;Masuoka et al 2019), inhibit the production of inflammatory cytokines by peripheral blood mononuclear cells (Katakura et al 2017), and enhance muscular strength and exercise endurance (Hirohiko et al 2006). Because avian muscle contains a large amount of anserine as noted previously, much evidence shows that consumption of a popular Asian food known as chicken essence (chicken meat extract) by humans, particularly elderly subjects, has long been a nutritional means to improve human health and prevent chronic diseases.…”
Section: Health Benefits Of Anserine Supplementationmentioning
confidence: 99%
“…insulin resistance (2 g/daily for 12 weeks, humans) [21], diabetic kidney disease (60 mg/kg for 20 weeks, rodents) [22], atherosclerosis (2 g/l drinking water for 20 weeks, rodents) [23], Alzheimer's disease (AD) (10 mM, in vitro) [24], Parkinson's disease (1.5 g for 30 days, humans) (PD) [25], and wound healing (100 mg/kg for 12 days, rodents) [26]. It is also interesting to note that in humans dietary supplementation with carnosine has produced beneficial outcomes in various aspects of behaviour and well-being [27][28][29][30][31][32]. Although such phenomenology does not provide any insight into the actual mechanistic route by which the dipeptide induces these effects, these observations nevertheless indicate that dietary carnosine can influence the brain despite the presence of serum carnosinase.…”
Section: Possible Anti-ageing Mechanisms Of Carnosinementioning
confidence: 96%
“…Supplementation with carnosine has been shown to have anti-inflammatory, antioxidant, antiglycation and chelating roles, and may act as a buffering agent in skeletal muscle and improve calcium handling [9][10][11][12]. Although circulating carnosine levels are affected by the presence of plasma carnosinase in humans [7], long-term supplementation of carnosine results in improved health and/or behavioural outcomes (27)(28)(29)(30)(31)(32). Therefore, it could be speculated that chronic supplementation maintains a more constant plasma level of carnosine mainly due to saturation of carnosinase.…”
Section: Introductionmentioning
confidence: 95%
“…We previously demonstrated that carnosine and anserine supplementation is capable of preserving cognitive function in elderly people using a double-blind randomized controlled trial [3]. Therefore, carnosine is expected to be recognized as a useful functional food factor.…”
Section: Supernatant Of U-87 Mg Cells Treated With Carnosine Induces mentioning
confidence: 99%
“…Chicken breast meat contains large amounts of imidazole dipeptide (IDP) (about 1% of chicken breast meat), of which carnosine (β-alanyl-L-histidine) and its derivative anserine (β-alanyl-1-methyl-L-hisitidine) are two types. IDP is known to have an anti-fatigue effect [1], to induce anti-depressant-like activity in rats [2], and to enhance memory function in elderly people [3]. Among IDPs, much research has focused on establishing the many functions of carnosine [4][5][6][7].…”
mentioning
confidence: 99%